The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jon.12684
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Atherosclerosis is Associated with Middle Cerebral Artery Pulsatility Index

Abstract: BACKGROUND AND PURPOSE Pulsatility index (PI) in the middle cerebral artery (MCA) is considered a measure of peripheral vascular resistance. Several established cardiovascular risk factors are common for both MCA PI and carotid atherosclerosis. Accordingly, in the present study we hypothesized an association between ultrasound‐derived indices of carotid atherosclerosis and MCA PI. METHODS All residents in Akershus County, born in 1950, were invited to a cardiovascular examination, The Akershus Cardiac Examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…However, the efficiency of treatment is insufficient. 5 , 6 Therefore, it is urgent to find therapeutic targets and deepen the understanding of carotid atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiency of treatment is insufficient. 5 , 6 Therefore, it is urgent to find therapeutic targets and deepen the understanding of carotid atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…We first sought to examine the impact of dietary intake of ω3 fatty acid in the development of obesity and atherosclerosis. To address this issue, we prepared 4 different types of diets; control diets that contain conventional amount 4% (wt/wt) of either soybean oil or linseed oil, and HFDs that contain lard and beef tallow which were supplemented with 10% (wt/wt) of either soybean oil or linseed oil, and maintained mice for 2 months on either the diet, and measured the body weight and pulsatility index and resistive index as indicators of the development of atherosclerosis [23][24][25] . We found that HFD-fed mice showed increased body weight when compared with control diet-fed mice, however, there were no differences between two types of dietary oils, suggesting that dietary ω3 fatty acids have no effect on the development of obesity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blood flow at the murine common carotid artery was visualized by Pulsed-Wave Doppler mode to measure peak-systolic velocity (PSV), endo-diastolic velocity (EDV) and time-averaged maximum flow velocity (TAMV; Vmean). Pulsatility index and resistive index were calculated by (PSV-EDV)/Vmean, and (PSV-EDV)/PSV, respectively [23][24][25] .…”
Section: Methodsmentioning
confidence: 99%
“…Increased pulsatile nature of arterial pressure by arterial stiffening promotes the influx of lipids into the subendothelial layer, plaque progression, and weakening of fibrous cap, which leads to plaque rupture [52,53]. The increase in PP accelerates carotid artery atherosclerosis and cerebral small vessel damage [54,55]. Shared risk factors (high blood pressure, hyperglycemia, dyslipidemia, smoking, inflammation, endothelial cell dysfunction oxidative stress, etc.)…”
Section: Pathophysiologymentioning
confidence: 99%